2011
DOI: 10.1093/bja/aeq317
|View full text |Cite
|
Sign up to set email alerts
|

Effects of epidural analgesia on uterine artery Doppler in labour

Abstract: Epidural analgesia using ropivacaine 1 mg ml⁻¹ (20 ml) significantly reduced placental blood flow only transiently during uterine contraction 30 min after the injection. These changes did not seem to affect neonatal outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…This concern was previously addressed in studies performing Doppler velocimetry of umbilical and uterine arteries during epidural analgesia in normal labour patients at term. However, the results were rather conflicting as some authors reported no change in uterine and foetal [4042] circulations, whereas others found a significant decrease in the resistance of the uterine and umbilical arteries [43]; others even reported an association between the epidural analgesia, maternal hypotension, and increased resistance indexes for the uterine arteries [44, 45]. The variations in reported findings are the likely result of substantially different study conditions.…”
Section: Discussionmentioning
confidence: 99%
“…This concern was previously addressed in studies performing Doppler velocimetry of umbilical and uterine arteries during epidural analgesia in normal labour patients at term. However, the results were rather conflicting as some authors reported no change in uterine and foetal [4042] circulations, whereas others found a significant decrease in the resistance of the uterine and umbilical arteries [43]; others even reported an association between the epidural analgesia, maternal hypotension, and increased resistance indexes for the uterine arteries [44, 45]. The variations in reported findings are the likely result of substantially different study conditions.…”
Section: Discussionmentioning
confidence: 99%
“…It should be considered that the flow data were obtained under general anesthesia (ketamine/azaperone). It is known that different anesthetic methods [28][29][30] and agents, e.g.,xylazine [31,32], may influence uterine and fetal blood supply. However, ketamine does not seem to affect uterine blood flow [33,34], whereas azaperone can cause moderate hypotension and lowering of heart rate in pigs [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…Two recent studies did not examine uterine artery resistance [14,20]. One comparing Doppler indices after a very large bolus of ropivacaine plus sufentanil with those in a control group without epidural analgesia in labor showed a significant increase in the uterine artery pulsatility index 30 minutes after the bolus [14].…”
Section: Discussionmentioning
confidence: 99%
“…One comparing Doppler indices after a very large bolus of ropivacaine plus sufentanil with those in a control group without epidural analgesia in labor showed a significant increase in the uterine artery pulsatility index 30 minutes after the bolus [14]. The other found that umbilical artery resistance was reduced during uterine relaxation but increased during contractions, whereas the reverse was true for the fetal MCA [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation